p-iodophenol-enhanced luminol chemiluminescent assay applied to discrimination between acute lymphoblastic and minimally differentiated acute myeloid (FAB-M0) or acute megakaryoblastic (FAB-M7) leukemias - da Costa, M.; Ximenes, Valdecir Farias [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Falcao, R. P.; Fonseca, Luiz Marcos da [UNESP] (Nature Publishing Group, 2004)
Introduction: In this report, we propose the application of the p-iodophenol-enhanced luminol chemiluminescent technique to the determination of peroxidase (myeloperoxidase and/or platelet peroxidase) activity in blasts of minimally differentiated acute myeloblastic leukemia (AML-M0) and acute megakaryoblastic leukemia (AML-M7).Methods: the frozen blast cells from 29 patients were thawed and submitted to the optimized protocol.Results: All cases of AML-M7 and AML-M0 exhibited integrated light emission greater than 73 (10(2) mV x s), which was the arbitrary cutoff point set for the discrimination between AML and acute lymphoblastic leukemia (ALL) (mean + 3 x s.d. of ALL samples, n = 10). In addition, five out of seven cases of AML-M0 showed results above the Cutoff point.Conclusion: This highly sensitive enhanced chemiluminescent technique may be applied to discriminate between ALL and AML-M7 or AML-M1 cases, and most AML-M0 cases. It is very simple, cheap and easy to perform compared to other procedures used to measure MPO activity in AML-leukemias including AML-M7 and AML-M0.
Keywords: acute myeloid leukemia (AML); acute lymphoblastic leukemia (ALL); chemiluminescence; luminol; p-iodophenol; myeloperoxidase (MPO); platelet peroxidase (PPO)